Molecular Characterization and RNA Interference Analysis of SLC26A10 From Nilaparvata lugens (Stål) - Zhang, Ruijuan; Ji, Jinliang; Li, Yabin; Yu, Jianbin; Yu, Xiaoping; Xu, Yipeng (Frontiers in Physiology, 2022)
SLC26A10 is a member of the SLC26 gene family, but its role in insects is still unclear. We cloned the SLC26A10 gene of Nilaparvata lugens (NlSLC26A10) and found NlSLC26A10 contained 11 transmembrane regions and a STAS domain. Expression pattern analysis showed NlSLC26A10 expression was more upregulated in adults than in nymphs, highest in the ovary. After injection of double-stranded RNA (dsRNA) of NlSLC26A10, the mRNA level of NlSLC26A10 significantly decreased and, consequently, the ovarian development of adult females was hindered; the amount and the hatchability of eggs and yeast-like symbionts in mature oocytes decreased. Further study showed that NlSLC26A10 might result in decreased juvenile hormone level and vitellogenin expression. These results indicate that NlSLC26A10 plays an essential role in the reproduction of N. lugens.